Accessibility and Socio-economic Impact Assessment of Television in Rural Haryana (Indian Journal of Extension Education, 2014)
The study was conducted on a sample of 200 respondents comprising of 100 males and 100 females drawn from four villages of Hisar district. The data were collected on structured interview schedule on television. A majority of male respondents had access to television, had complete control on use of television, had no control on selling and purchase of television. Cent per cent of female respondents had no control on selling and purchase of television whereas a majority of female (82.00%) respondents had complete control on use of television. As far as personal life of rural respondents is concerned in case of male respondents television had increased awareness on current news and general awareness, provided entertainment, and changed fashion perception where as in case of personal life of female respondents television had high impact in the areas of entertainment, current news/general awareness and decision making ability. Regarding social life of rural male respondents, television had high impact in areas of social awareness, awareness about domestic violence and social messaging whereas in case of social life of female respondents television had high impact in areas of social awareness, social status and level of social acceptance.Television had high impact on life of male and female respondents in the field of education which included career information, job opportunities and awareness about admissions. As far as economic aspect is concerned television had positive impact on the aspects like market information, financial management and women’s increased access to jobs. Regarding female respondents, television had higher impact on financial management, market information and personal and business contact. Impact of television on health and political aspect reveals that television had high impact on awareness about diet/nutrition, meditation/yoga where as it had moderate impact on awareness about diseases. Regarding female respondent’s television had high impact on awareness about diet/nutrition, moderate impact on awareness about diseases and awareness about medicines. Regarding agricultural aspect it was found that television had high impact on life of the male respondents in terms of improvement of sales, information on crop production and preventing crop diseases whereas television had moderate impact on preventing crop diseases, live stock keeping and animal fertility. Association of socio-economic variables of male and female respondents with access to television revealed that there was no significant association of age, education and occupation on access to television. Association of socio-economic variables of male and female respondents for those who had control on television revealed that there was significant association of education with control of television. Significant association of complete access to impact of television, complete control on use of television & impact of television and partial control on selling and purchase of television & impact of television was observed. Main constraints in use of mobile were economic dependency, lack of decision making ability, lack of control on use of mobile and lack of power supply.